Can co-creation in extended reality technologies facilitate the design process?. Issue 2 (9th July 2020) - El-Jarn, Hatana; Southern, Glen
Abstract : Purpose: The purpose of this paper is to explore the benefits of co-creation/co-design using extended reality (XR) technologies during the initial stages of the design process. A review of the emerging co-creation tools within XR will be examined along with whether they offer the potential to improve the design process; this will also highlight the gaps on where further research is required. Design/methodology/approach: The paper draws on professional and academic experiences of the authors in creative practices within the realm of XR technology, co-creation and co-design. In addition, a review of the current literature on emerging technologies and work-based learning will offer further insight on the themes covered. Findings: To design, collaborate, iterate and amend with colleagues and peers in a virtual space gives a wide range of obvious benefits. Creative practitioners both in education and employment are working more collaboratively with the advancement of technology. However, there is a need to find a space where collaboration can also offer the opportunity for co-creation that improves the initial stages of the design process. This technology also offers solutions on the constraints of distance and ameliorates creative expression. Research limitations/implications: There is an opportunity to test the ideas expressed in this paper empirically; this can be done through testing co-creation tools with professionals, work-based learners and students. Originality/value: The paper will add to the existing literature on emerging technologies as a unique environment to improve co-create/co-design the visuals created during the fuzzy front end of the design process and offer a potential framework for future empirical work.